Some Equivalences between Cone b-Metric Spaces and b-Metric Spaces - Poom Kumam; Nguyen Van Dung; Vo Thi Le Hang (Abstract and Applied Analysis)
We introduce a b-metric on the cone b-metric space and then prove some equivalences between them. As applications, we show that fixed point theorems on cone b-metric spaces can be obtained from fixed point theorems on b-metric spaces.